The king's army : warfare, soldiers, and society during the wars of religion in France, 1562-1576 - Wood, James B., 1946- (Cambridge studies in early modern history., 1996)
Historians have long ignored the military aspect of the wars of religion which raged in France during the late sixteenth century, dismissing the conflicts as aimless or hopelessly confused. In contrast, this meticulously researched analysis of the royal army and its operations during the early civil wars brings warfare back to the centre of the picture. James B. Wood explains the reasons for the initial failure of the monarchy to defeat the Huguenots, and examines how that failure prolonged the conflict. He argues that the nature and outcome of the civil wars can only be explained by the fusion of religious rebellion and incomplete military revolution. This study makes an important contribution to the history of military forces, warfare and society, and will be of great interest to those engaged in the debate over the 'Military Revolution' in early modern Europe.